2008
DOI: 10.1177/0003319708318383
|View full text |Cite
|
Sign up to set email alerts
|

Do Different Vascular Risk Factors Affect All Arteries Equally?

Abstract: This editorial discusses the prognostic role of the established risk factors in different vascular diseases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
18
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 56 publications
(83 reference statements)
1
18
0
Order By: Relevance
“…These findings are in contrast to our results, wherein we observed a directionally proportional increase in PP with BMI. Smoking is a major risk factor for all vascular diseases [3,4,9,10,47]. In our study, the effect of current smoking on PP was only observed in white men.…”
Section: Discussionmentioning
confidence: 42%
See 2 more Smart Citations
“…These findings are in contrast to our results, wherein we observed a directionally proportional increase in PP with BMI. Smoking is a major risk factor for all vascular diseases [3,4,9,10,47]. In our study, the effect of current smoking on PP was only observed in white men.…”
Section: Discussionmentioning
confidence: 42%
“…Contrary to its role as a risk factor for hypertension, moderate alcohol consumption may provide a protective effect in reducing PP and reduced risk of cardiovascular events. This finding should be evaluated with extreme caution because heavy alcohol consumption has been associated with a high prevalence of metabolic syndrome, diabetes mellitus, peripheral artery disease, stroke, CHD and other social ills [9,49].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These considerations have an even higher impact when associated with endothelial activation and dysfunction as characterized by increased levels of circulating oxidized LDL, intercellular and vascular adhesion molecules and CRP, and with the evidence that vascular complications are also associated with OxS events [152]. In addition, the role of OxS may vary depending on the distribution of vascular receptors in different anatomical sites [150,153].…”
Section: Endothelial Oxidative Dysfunction and Hypertensionmentioning
confidence: 99%
“…12,13 Smoking reverses the beneficial effects of primary and secondary prevention measures; in patients with IHD taking aspirin, cigarette smoking acutely increases platelet thrombus formation. 14 Smoking also diminishes the beneficial effect of statins on the cardiovascular system, 15 besides increasing the risk of developing diabetes mellitus.…”
mentioning
confidence: 99%